Ahaptoglobinaemia in a Nigerian Cohort (Nigerian Journal of Physiological Sciences, 2018)
Summary: Ahaptoglobinaemia have been indicated in blacks from West Africa. Owing to the clinical and biologic importance of haptoglobin (hpt), this work explores the situation in a Nigerian cohort since there are no published values of haptoglobin levels of individuals in this locality. The study was aimed at determining the amount of haptoglobin in the blood of normal healthy Nigerians. Haptoglobin was quantitatively estimated in one hundred and fifty-two apparently healthy individuals using highly sensitive immunoassay technology. Blood grouping and haemoglobin genotype were assayed for all subjects to know if they influence haptoglobin levels. The association between haptoglobin and blood group was also established. Serum levels of haptoglobin among all subjects analyzed revealed a marked decrease in their haptoglobin levels when compared to other reference intervals. A further association between haptoglobin and gender did not reveal a statistical significant relationship (p>0.05). However, there was a significant different when haptoglobin levels of different blood groups and haemoglobin genotype when compared. Our data suggest that serum levels of haptoglobin are significantly lower in healthy Nigerians. The lower limit was remarkably lower than the internationally acceptable Caucasian reference range suggesting a clear necessity for establishing reference African values.